Biochemistry and biotechnology of fermented foods - Nguyen Minh Nhut (Delve Publishing, 2017)
Traditional fermented foods contribute greatly to the healthy food sources for human being. Historically, fermentation is a universal practice that our ancestors used to extend the food shelf life, to improve the palpability and importantly to provide medicinal properties. When the healthy value of fermented foods is gradually recognized, intensive throughput of biotechnological researches have been applied into many fermentative aspects, such as starters’ working mode and functional genes, starters’ applications in other industries, nutritional improvements of fermented products and more. With the purpose of covering fundamental aspects of fermented foods, the first part of this book will discuss classical fermented starters and their applications, relating to lactic acid bacteria, acetic acid bacteria, yeast and fungi as well as popular fermented products thereof. Beer, bread, kefir, fermented milks products, meats and fermented vegetables will be discussed into details. The second part of this book will focus mainly on the trending researches of fermented foods, involving nutritional and medical value gained from their metabolites like probiotics, carotenoids and flavonoids production, and using the starters in food modifications. Interestingly, several starters such as yeast is capable of carotenoids production in massive scale, which is believed to replace natural carotenoids from plants in a near future. The last part will get into insight of fermented starters by analyzing their genomes, which could reveal a brighter perspective in fermented food researches in next decades.--Provided by publisher.